Application of the Problem Based Learning Model to Improve Social Studies Learning Outcomes for Class VII Students at SMPN 2 Cibiuk - Dewi Susilawati, Dewi Susilawati; Ade Suherman; Lili Dianah (SAHUR Journal, 2024)
This research is motivated by the main problems that occur in students who have the notion that social studies is a very boring subject and there are not a few students who try to avoid these subjects. Then the learning method applied by educators is still conventional with the Teacher Centered Learning (TCL) approach. The purpose of this research is to identify that there is an increase in social studies learning outcomes when using the problem based learning model. The research method used is a quantitative method with a type of quasi-experimental method. As for the results of this study it can be identified that there is a significant increase in learning outcomes when applying the problem-based learning model, then the results of data analysis and statistical calculations using the Likert scale show that the attitude of students towards the problem-based learning model in general shows a very good attitude and the attitude of students towards the problem-based learning learning model each individual shows a very good attitude, it can be concluded that the interpretation of the student's attitude scale towards the problem-based learning learning model is in the very good category. Therefore the problem-based learning model is effective in improving student learning outcomes.